2017
DOI: 10.1002/ejic.201700265
|View full text |Cite
|
Sign up to set email alerts
|

Introducing Chirality into Hybrid Clusters from an Achiral Ligand: Synthesis and Characterization of Polyoxomolybdates Containing a Benzylarsonate Group

Abstract: Benzylarsonic acid as a flotation collector was introduced into polyoxometalate chemistry and two new hybrid clusters, [(C 6 H 5 CH 2 AsO 3 ) 2 Mo 5 O 15 ] 4-(1a) and [(C 6 H 5 CH 2 AsO 3 ) 4 -Mo 12 O 34 ] 4- (2a), were synthesized and characterized by chemical and spectral analysis. Self-assembly of 1a led to chiral crys- [a]

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 49 publications
0
3
0
Order By: Relevance
“…Phenylarsonic acids are isoelectronic to phenylphosphonic acids yet have not been explored as electronic modulators of redox-rich tungstate-based POMs. In fact, only a small number of examples exist where polyoxotungstates have been functionalized with organoarsenic groups, and these have mainly served as structural motifs for accessing new cluster morphologies. …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Phenylarsonic acids are isoelectronic to phenylphosphonic acids yet have not been explored as electronic modulators of redox-rich tungstate-based POMs. In fact, only a small number of examples exist where polyoxotungstates have been functionalized with organoarsenic groups, and these have mainly served as structural motifs for accessing new cluster morphologies. …”
Section: Introductionmentioning
confidence: 99%
“…In fact, only a small number of examples exist where polyoxotungstates have been functionalized with organoarsenic groups, and these have mainly served as structural motifs for accessing new cluster morphologies. 23 31 …”
Section: Introductionmentioning
confidence: 99%
“…Our group is interested in functional POM and POM hybrid molecules, and we have demonstrated that using benzylarsonate to construct the POM hybrid could introduce additional chirality into the hybrid compound in either the formation of a conventional bond or supramolecular packing. 25 In an effort to understand the self-assembly process and configuration control, herein we extended the study to polyoxotungstate systems, and a n e w t r i a n g u l a r P O M h y b r i d c a g e c l u s t e r , [ ( C 7 H 7 A sO 3 ) 6 W 1 2 O 3 6 ] 1 2 − ( 1 a ) , w a s is o l a t e d a s Na 2 (C 2 H 8 N) 4 H 6 [(C 7 H 7 AsO 3 ) 6 W 12 O 36 ]•30H 2 O (1; CCDC 1814918). Unexpectedly, 1a reorganized into the isomer 2a when it was further protonated.…”
mentioning
confidence: 99%